Eurasian ice sheet formation promoted by weak AMOC following MIS 3 - Lu Niu; Gregor Knorr; Lars Ackermann; Uta Krebs-Kanzow; Gerrit Lohmann (npj Climate and Atmospheric Science, 2025)
Abstract The Eurasian ice sheet complex (EIS) was the third largest ice sheet complex at the Last Glacial Maximum (LGM). Although temporal and spatial evolution of the EIS during the last glacial cycle has not been well-established, strong evidence indicates the existence of nearly ice-free conditions during Marine Isotope Stage 3 (MIS 3). Between MIS 3 and the LGM, the EIS likely experienced substantial expansions. These expansions were accompanied by decreasing boreal summer insolation, a slight reduction in greenhouse gases, and millennial-scale abrupt shifts between stadial and interstadial conditions. Using the state-of-the-art Earth system model AWI-ESM with asynchronously coupled dynamic ice sheets, we performed transient simulations focusing on this period. Our study shows that the formation of the EIS resembles a bifurcation transition. Only in case of a relatively weak background Atlantic Meridional Overturning Circulation (AMOC), a sufficiently large thin ice/snow cover develops to accommodate a subsequent ice volume growth as Northern Hemisphere summer insolation further decreases. Furthermore, sensitivity experiments show a large non-linearity in surface mass balance changes in response to varying temperature and precipitation, indicating a high sensitivity of the EIS buildup. Our study highlights the large complexity and strong non-linearity of the Earth system induced by internal climate feedbacks, particularly the interactions between ice sheets and other climate components.